(untitled) (International Journal of Environmental Sciences, 2025)
The interrelationship between environmental ecology, biodiversity, and climate change is becoming increasingly critical in shaping modern disaster management strategies. Escalating global temperatures, altered precipitation patterns, and habitat disruptions have intensified the frequency and severity of natural disasters such as floods, droughts, cyclones, and wildfires. Biodiversity loss further compromises ecosystem resilience, weakening natural buffers like wetlands, forests, and coral reefs that mitigate disaster impacts. This paper explores the integrated dynamics between ecological degradation and climate change, emphasizing their cumulative effects on disaster risk and management frameworks. Drawing from multidisciplinary approaches and recent global case studies, the research examines how ecosystem-based disaster risk reduction (Eco-DRR), nature-based solutions (NbS), and climate-adaptive planning can build sustainable resilience in vulnerable regions. The study argues for the necessity of embedding biodiversity conservation and ecological restoration into climate policies and disaster preparedness plans to ensure long-term environmental and human security.